2006
DOI: 10.1007/s00384-006-0228-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemotherapy in microsatellite unstable (MSI-H) colorectal cancer

Abstract: Available evidence suggests that MSI-H CRC have different behaviour patterns and response to chemotherapy compared with MSS CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 81 publications
1
47
1
1
Order By: Relevance
“…Current treatment of small bowel adenocarcinoma commonly includes surgical resection and adjuvant 5-fluorouracil as it is standard in colorectal cancer (1). It has been reported that microsatellite instability-positive colorectal cancer does not response to treatment with 5-fluorouracil as well as microsatellite stable colorectal cancer (48). Because our study and others showed that the frequency of microsatellite instability in celiac disease-related small bowel adenocarcinomas is much higher (43-73%; refs.…”
Section: Discussionmentioning
confidence: 56%
“…Current treatment of small bowel adenocarcinoma commonly includes surgical resection and adjuvant 5-fluorouracil as it is standard in colorectal cancer (1). It has been reported that microsatellite instability-positive colorectal cancer does not response to treatment with 5-fluorouracil as well as microsatellite stable colorectal cancer (48). Because our study and others showed that the frequency of microsatellite instability in celiac disease-related small bowel adenocarcinomas is much higher (43-73%; refs.…”
Section: Discussionmentioning
confidence: 56%
“…It is recognised that defective DNA mismatch repair (MMR) leads to MSI and results in resistance to many antineoplastic drugs, such as antimetabolites, alkylating, and platinum agents, and inhibitors of topoisomerases. There are some evidences in vitro that suggest a correlation between response to 5-FU, OXA, and IRI and MSI (Magrini et al, 2002;Arnold et al, 2003;Warusavitarne and Schnitzler, 2007). Our analysis plan did not include an MSI analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies investigating the effect of 5-fluorouracil and survival in MMR-deficient colorectal cancer have mainly been retrospective and derived from unselected nonrandomized groups and therefore potentially biased (21). However, Ribic et al who analyzed 570 tissue specimens of stage II and III colorectal cancer from pooled randomized controlled trials described no advantage to 5-fluorouracil treatment in patients with MSI-H colorectal cancers (22).…”
mentioning
confidence: 99%